2022
DOI: 10.3390/jof8020137
|View full text |Cite
|
Sign up to set email alerts
|

The Multilateral Efficacy of Chitosan and Trichoderma on Sugar Beet

Abstract: The majority of all fungal formulations contain Trichoderma spp., making them effective biological control agents for agriculture. Chitosan, one of the most effective natural biopolymers, was also reported as a plant resistance enhancer and as a biocide against a variety of plant pathogens. An in vitro three-way interaction assay of T. atroviride, chitosan, and important plant pathogens (such as Cercospora beticola and Fusarium oxysporum) revealed a synergistic effect on fungistasis. Furthermore, chitosan coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
(102 reference statements)
1
14
0
Order By: Relevance
“…Priming of cucumber with chitosan induced deposition of lignin and callose, enhanced the accumulation of defense-responsive enzymes, and increased disease resistance against powdery mildew (Jogaiah et al, 2020). Chitosan-primed sugar beet plants exhibited upregulation of PR3, PAL, and GST genes, as well as enhanced resistance against CLS disease (Kappel et al, 2022). Rice primed with CAGCs induced expression of defense genes EDS1, ICS1, NPR1, MKK4, and PR1 genes, and enhanced resistance against rice bacterial leaf blight disease (Pal et al, 2021).…”
Section: Strategies and Challenges In Exploiting Seed Priming To Impr...mentioning
confidence: 99%
See 3 more Smart Citations
“…Priming of cucumber with chitosan induced deposition of lignin and callose, enhanced the accumulation of defense-responsive enzymes, and increased disease resistance against powdery mildew (Jogaiah et al, 2020). Chitosan-primed sugar beet plants exhibited upregulation of PR3, PAL, and GST genes, as well as enhanced resistance against CLS disease (Kappel et al, 2022). Rice primed with CAGCs induced expression of defense genes EDS1, ICS1, NPR1, MKK4, and PR1 genes, and enhanced resistance against rice bacterial leaf blight disease (Pal et al, 2021).…”
Section: Strategies and Challenges In Exploiting Seed Priming To Impr...mentioning
confidence: 99%
“…Seed priming could secure the enhanced and uniformed seed germination and seedling establishment under field conditions, and greatly contributes to the improvement of crop growth and production (Marthandan et al, 2020;Johnson and Puthur, 2021). Increasing evidence revealed that seed priming could induce plant immune memory that is either stably maintained throughout developmental stages or transmitted over generations (Jogaiah et al, 2020;Joshi et al, 2021;Martínez-Aguilar et al, 2021;Pal et al, 2021;Yadav et al, 2021;Kappel et al, 2022). As summarized in Table 1, different types of seed priming approaches such as biological priming, chemical priming, and nanomaterials priming have been successfully established to protect crop plants against pathogen infections.…”
Section: Strategies and Challenges In Exploiting Seed Priming To Impr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Seed dressing is another potential application of chitosan to reduce disease [191]. Interestingly, chitosan showed a synergistic effect with some biocontrol agents such as Trichoderma spp., indicating both castor seed protection [192] and a increased reduction in the pathogenicity of Cercospora beticola and Fusarium oxysporum [193]. Chitosan should also be added to the soil to reduce the severity of tomato crown and root rot caused by Fusarium oxysporum f. sp.…”
Section: Natural Productsmentioning
confidence: 99%